Analytical assessment of sea ice-induced frequency lock-in for offshore wind turbine monopiles. (July 2018) - Seidel, Marc; Hendrikse, Hayo
Abstract: In this paper, an analytical method is presented to assess FLI (Frequency lock-in) of monopile support structures for offshore wind turbines, subjected to loading by floating sea ice. The method is introduced, justified and presented with an example. The main idea of the method is to use existing knowledge regarding structural response velocities at which FLI can occur. Using such velocities, the structural response can be determined easily when single mode response is assumed, which is a conservative choice when analyzing FLI. The method is particularly useful for early stages of the design process, when the implication of ice loads on the design needs to be assessed without time-consuming simulations. Results from the method can also be used to identify structural configurations which are most critical for ice loading. Highlights: An analytical method is presented to assess FLI (Frequency lock-in) of monopile support structures for offshore wind turbines. The method uses existing knowledge regarding structural response velocities at which FLI can occur. Using such velocities, the structural response can be determined easily when single mode response is assumed. The method is particularly useful for early stages of the design phase. Results from the method can also be used to identify structural configurations which are most critical for ice loading.